Kesan pewartaan taman laut ke atas penduduk Pulau Tinggi, Mersing, Johor - Azima Abdul Manaf; Mohd Samsuddin; Mustaffa Omar (2011)
Marine Park Malaysia is endorsed under Section 41- 45 Fishing Act 1985. Realization of the Marine Park Malaysia in 1994 brings 40 islands under its protected area. Among these are islands of Pulau Redang and Pulau Perhentian in Terengganu, Islands of Payar in Kedah, the islands of Tioman in Pahang and islands of Pulau Tinggi in Johor. The establishment of Marine Park Malaysia is to protect and conserve various habitat and aquatic marine life especially coral, flora and fauna. Marine Park Malaysia is endorsed by law and legislation to protect the natural resources around the island and its surrounding. Declaration of Pulau Tinggi as the Marine Park has honoured the efforts to protect natural heritage as well as to enhance the economy of the local people. However, it also has caused some problems to the people inhabiting these islands. This article examines the steps taken to gazette Pulau Tinggi islands as a Marine Park and its impact on the local peoples. It also discusses problem and challenges faced by the peoples as a result of its endorsement under the protected area of Marine Park